Analytical Study of Factors Influencing the Implementation of the Team-Model Professional Nursing Care Method at HNGV, Timor-Leste, 2025 - Oqui, Maximiano; Beremane, Heliodoro Goncalves; Conçeição, José Ximenes da; De Jesus Araujo, Agostinho Maria; C. Gaio, Eduardo; Corte Real Araújo, Artur Natalino; Fernandes, Manuel da Costa (Rifa'Institute, 2025)
Introduction: The Professional Nursing Care Method (PNCM) of Team Model is an approach that emphasizes collaboration between nurses in providing quality nursing care. However, the implementation of this method often faces various challenges, such as ineffective leadership, suboptimal supervision, limited knowledge, low motivation, and high workload. Objective: to analyze the factors that influence the implementation of Professional Nursing Care Method (PNCM) of Team Model in Inpatient Ward, National Hospital Guido Valadares, Dili, Timor-Leste, Year 2025. Methods: Using analytic design with a cross-sectional study approach. The total population was 93 nurses, and a sample of 76 nurses was taken using stratified random sampling technique. Results and Discussion: The partial hypothesis analysis showed that leadership (p = 0.007, OR = 4.15) and knowledge (p = 0.000, OR = 19.77) had a significant positive influence on the application of the PNCM team model, while workload had a significant negative effect (p = 0.032, OR = 0.28). In contrast, supervision (p = 0.094) and motivation (p = 0.254) showed no significant partial influence. Simultaneously, leadership, supervision, knowledge, motivation, and workload contributed 37.8% to the application of the Professional Nursing Care Method (PNCM) of the Team Model. Conclusion: Leadership, knowledge, and workload factors have a partial influence to the Application of Professional Nursing Care Method (PNCM) of Team Model, but supervision and motivation factors have no partial influence, at the simultaneous test stage it was found that all factors had a simultaneous influence to the Application of Professional Nursing Care Method (PNCM) of Team Model.